A comprehensive investigation of distribution in the context of workflow management - Jablonski, S.; Schamburger, R.; Hahn, C.; Horn, S.; Lay, R.; Neeb, J.; Schlundt, M. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Distribution is often discussed under different issues of interest in the context of workflow management. This paper contributes a general framework for this discussion, i.e. it presents a general framework for workflow management in distributed environments. Technical and organizational issues are analyzed that have an impact on the design of a distributed workflow management system. Within the core part of the paper we present a taxonomy enabling to compare implementation concepts of different workflow management systems especially with respect to distribution.